Lack of information received by a French female cohort regarding prevention against exposure to reprotoxic agents during pregnancy. (October 2016) - Chabert, Marie-Charlotte; Perrin, Jeanne; Berbis, Julie; Bretelle, Florence; Adnot, Sébastien; Courbiere, Blandine
Abstract: Objective: The aim of this study was to evaluate the information pregnant women received regarding possible exposures to five recognized reprotoxic agents during their pregnancy. Study design: A cohort study was conducted using two postnatal units in France. Women hospitalized in postnatal units were requested to complete a self-administered two part questionnaire. The first part gathered information about the patient's socio-professional level and the type of pregnancy follow-up. The second part examined the information the patient received regarding daily products containing the following known reprotoxic agents: bisphenol A, toluene, n -hexane, cis -chloroallyl-triaza-azonia-adamantane-chloride and O -phenyl-phenol. The women cited the sources of information. We combined the employment status and educational level to separate the women into two groups. The groups were then compared using the Chi Square test or Fisher's exact test. Result(s): There were 390 women in this study. Our results showed the women received information regarding the following: 21.6% ( n = 84) regarding tin cans, 21.9% ( n = 85) concerning plastic meal boxes when heated in microwave ovens, 8.8% ( n = 32) about water in gas-bottles, 27.4% ( n = 106) about non-organic foods, 39.3% ( n = 152) about hair dyes, 17% ( n = 66) about nail polishes, 23.4% ( n = 103) about insect repellents, 34.4% ( n = 133) about "do-it-yourself" products, 2.1% ( n = 8) about gardening products, 26.7% ( n = 103) about electric plug-in repellents, 21.1% ( n = 81) about housekeeping products, and 6.8% ( n = 26) about register receipts. Women with a higher level of education and a qualified occupation were better informed about these daily products. These women were more likely to learn the information on their own (internet, media). Conclusion(s): Our study showed French women did not receive sufficient information regarding potential exposures to reprotoxic agents during pregnancy.